Structural Analysis of Masonry Square Vaults in the Italian Region of Apulia - Maristella De Fabrizio; Vincenzo Mallardo (Buildings, 2023)
This research concerns the introduction and the structural analysis of masonry vaults in Puglia, a region in the south part of Italy, built between the sixteenth and the seventeen centuries. Such vaults have special shapes that make them unique in the overview of the masonry vaults spread all over the world. The present paper intends to shed light on the mechanical behavior of two typical vaults in Puglia, the “volta a spigoli” (edge vault) and the “volta a squadro” (square vault). There are many contributions that explore the mechanical behavior of the classical vaults, but to the authors’ knowledge, this is the first attempt investigating the “volta a squadro”. The paper describes the adopted research methods. First, a building survey is carried out with the integration of previous geometry acquisitions performed by local stakeholders. Then, the analysis is pursued by a non-linear approach that suitably inserts cracks where stress concentrations occur. Two meaningful load conditions are taken into account and numerically investigated. Under vertical loads, numerical results have inferred the surveyed cracks and concluded that the safety factor is much higher than one. On the other hand, under the maximum seismic load, the safety factor is estimated to be about 30%. This work is the very first investigation on the structural performance of a “volta a squadro”.